2020
DOI: 10.21203/rs.3.rs-70890/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ethnozoological Study of Traditional Medicinal Animals and Their Products Used by The People of South Achefer District, Northern Ethiopia

Abstract: Background: There is an ancient history that human beings are familiar with use of animals and plants for food, cloth, medicine, etc. In Ethiopia, many ethnic communities which are dispersed all over the country has been totally dependent on local traditional medicinal system for their health care. Thus, the aim of this study was to take an ethnozoological field survey among different ethnic groups that live in South Achefer district. In order to document the ethno zoological information about animal and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Chellappandian et al (2014) also reported its use against jaundice from Tamil Nadu in India. Mola et al (2020) reported the use of milk against cough in Ethiopia.…”
Section: Species and Usage With Respect To Changapamentioning
confidence: 99%
“…Chellappandian et al (2014) also reported its use against jaundice from Tamil Nadu in India. Mola et al (2020) reported the use of milk against cough in Ethiopia.…”
Section: Species and Usage With Respect To Changapamentioning
confidence: 99%
“…Tus, the country is one of the most biodiversity-rich countries in the world [8]. Shreds of evidence showed that Ethiopia owns the ffth-largest foral composition in tropical Africa [9].…”
Section: Introductionmentioning
confidence: 99%